Quasilegality and migrant smuggling in Northern Niger - Frowd, Philippe M. (Trends in organized crime, 2023)
Niger’s status as a ‘hub’ for West African migration is now cemented in the imaginaries of interveners and global observers. Even as the number of migrants transiting the country falls sharply from a peak in 2015, the policies and practices on the part of the Nigerien government, its local partners, and international actors, continue to coalesce around irregular migration as a major security priority. This mostly repressive approach to irregular migration has had knock-on effects on livelihoods in Northern Niger, where the bulk of the economy around transiting migration is rooted. While the story of criminalization and securitization in Niger is a well-worn one, there is less attention to some of the ways these processes are incremental, erratic, incomplete, ambiguous, and contested. This article argues that once we consider the voices of market insiders in the smuggling economy alongside those in the security and intervention sector, these narratives point to the fundamentally ambiguous status of the migration economy between the licit and illicit, the legal and the illegal. To capture this ambiguity, the article draws on the concept of quasilegality, which captures the in-between status of the flows in question, and in particular the conceptual space between the licit/illicit and legal/illegal binaries. Quasilegality points to three salient factors in contesting the straightforward narrative of criminalization in Niger: a gap between the social acceptability of smuggling and state legal frameworks, the ambiguity of the state legal framework and its application, as well as market insiders’ own understanding of their activities. The article’s attention to narratives around migration, crime, and (in)security in Niger is at once a means of complicating the smoothness of security and control as well as a broader critique of views of migration in Niger that would see it as a straightforward example of ‘transnational organized crime’ in West Africa.